Mengembangkan Kecerdasan Spiritual dan Sosial Melalui Evaluasi Hasil Belajar Pendidikan Agama Islam Siswa MAN 2 Jember - Wahidah, Nur; Afida, Ifa (AS-SUNNIYYAH, 2022)
Intelligence is the ability to understand the world, think rationally, and use effective resources when faced with challenges. the contents of the Act above indicates that the function of education as a formation of personality that reflects the values of high nobility is more focused to form students who are intelligent spiritual and intelligent in social. Developed spiritual intelligence through evaluation of learning result of Islamic education of student MAN 2 Jember is to develop spiritual intelligence on the behavior of believers and cautious, and than develop spiritual intelligence on grateful behavior. whereas To develop social intelligence through evaluation of learning result of Islamic education of student MAN 2 Jember is develop social intelligence on honest, The attitude of discipline, responsibility attitude, Caring attitude (tolerance and gotongroyong), Good manners and The attitude of self-confidence.